Eksistensi Makam Syekh Mahmud Al-Muhtazam sebagai Wisata Religi di Desa Pananggahan Kecamatan Barus Utara Kabupaten Tapanuli Tengah - Lathifah, Siti; Hasanah Siregar, Nidaul; Micola, Airlangga (Tadbir: Jurnal Manajemen Dakwah, 2025)
This study discusses the existence of the Tomb of Sheikh Mahmud Al-Mutahzam as a religious tourism destination in Pananggahan Village, North Barus District, Central Tapanuli Regency. Sheikh Mahmud was a cleric from Hadramaut, Yemen, who is estimated to have come to the Archipelago in the 7th century and played an important role in the spread of Islam in the Barus region. His tomb is located on Papan Tinggi, a hill known as the "Thousand Steps", and is a spiritual symbol and a relic of early Islamic history in Indonesia. This study uses a qualitative approach through field studies and literature, including interviews with tomb guards and direct observation of the tomb site. The results of the study show that the existence of the tomb not only strengthens the spiritual identity of the local community but also has an economic impact through visits by pilgrims and tourists. In addition, the presence of tombstones with ancient Arabic-Persian inscriptions strengthens the historical authenticity of this site. This study emphasizes the importance of preserving tombs as part of the cultural and historical heritage of Islam in the Archipelago.